EFFET DE L’ACIDE BORIQUE SUR LA CROISSANCE DE LA ROSELLE (HIBISCUS SABDARIFFA L. VAR. SABDARIFFA) AU GABON - Alexis Nicaise Lepengue; Jacques Francois Mavoungou; Alain Souza; Bertrand M’batchi (European Scientific Journal, ESJ, 2013)
Roselle is the one of gabonese major vegetable crop plant, where it is cultivated for alimentary and medicinal reasons. In order to intensify agronomical production of this plant, boric acid (H3BO3) inductions effects are tested by measuring seed germination, longitudinal and diameter growth, and leaf area. The results showed that boric acid increased all morphometric parameters evaluated at low concentrations, below 10-6 M. However, it was noted that at concentrations above 10-5 M, this compound rather inhibited the growth parameters measured. These actions should be resulted from boron presence in boric acid molecule chemical formulation. Lower boric acid concentration treatments (particularly 10-6 M) should be used to ameliorate roselle growth and production.